Length-weight Relationship and Relative Condition Factor of Paratrypauchen microcephalus (Bleeker, 1860) along the Mumbai Coast - Pujari, Ruchi; Gore, B.M.; Jumale, S.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The length-weight relationship and relative condition factor of Paratrypauchen microcephalus (Bleeker, 1860) from Madh, Mumbai, was studied between October 2021 and December 2022. A total of 179 fish were examined, which included 81 males, 75 females, and 23 juveniles. The relationship between total length and weight was estimated by the least squares method, and the results indicated that the species exhibits a negative allometric growth pattern, with the exponent ‘b’ values obtained being 1.1545 for males, 1.1728 for females, 1.0260 for juveniles, and 0.9443 for the pooled observations. The regression values obtained were highly significant (P < .01), showing a good relationship between the length and weight of this fish. The mean value for the relative condition factor (Kn) obtained during the study was 0.5757, 0.6610, and 2.4730 for males, females, and juveniles, respectively, reflecting that males and females are not in a better health condition while juveniles are, having a Kn value greater than 1. The current study thus provides the first baseline data about LWRs and the relative condition factor of this fish species from the Mumbai coast.